Analysis of Influence Factors of Negative Skin Friction on PHC Pile in High-Backfill Sites - Gen, Xiong; Ben, He; Bing, Pan; Xiangming, Ge; Weijiang, Chu (Frontiers in Physics, 2022)
It is recognized that NSF on a pile affects the structural and geotechnical design. The formation of NSF on a pre-stressed high-strength concrete (PHC) pile under a control building in a Vietnamese project was investigated using a verified numerical model in FLAC3D. The height of backfills, the consolidation degree of soil, working loads on the PHC pile, and the pile diameter were analyzed in sensitivity analyses to investigate the influence on NSF. It was found that higher backfills and higher consolidation degree were dominant in the formation of NSF, causing an increase of the dragload and an upward movement of the neutral plane. The working load and the pile diameter affected the dragload and the position of the neutral plane less. A limit decrease of the dragload induced by NSF was observed when the working load increased. Accelerating the soil consolidation process would be suggested to avoid great displacement due to NSF.